2017
DOI: 10.1242/dev.140657
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-2 binding protein 1 is a context-specific positive regulator of Notch signaling during neurogenesis inDrosophila melanogaster

Abstract: The role of the Notch pathway during the lateral inhibition that underlies binary cell fate choice is extensively studied, but the context specificity that generates diverse outcomes is less well understood. In the peripheral nervous system of Drosophila melanogaster, differential Notch signaling between cells of the proneural cluster orchestrates sensory organ specification. Here we report functional analysis of Drosophila Ataxin 2-binding protein 1 (A2BP1) during this process. Its human ortholog is linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…ppk23 is a modifier of flies' ability to track odors during free flight, but not a modifier of odorless flight [140]. Our results support a role for ppk23 in modifying flight, along with all but eight (Or46a, Ten-a), and transcription factors (A2bp1/ Rbfox1, CG42741, twi) [141,142], several of which had significant epistatic interactions of their own. Of these, CG10936 is proposed to be involved in sensory perception [142], but has limited annotations otherwise.…”
Section: Important Implications For Acid Sensing Ion Channels In Fligsupporting
confidence: 51%
“…ppk23 is a modifier of flies' ability to track odors during free flight, but not a modifier of odorless flight [140]. Our results support a role for ppk23 in modifying flight, along with all but eight (Or46a, Ten-a), and transcription factors (A2bp1/ Rbfox1, CG42741, twi) [141,142], several of which had significant epistatic interactions of their own. Of these, CG10936 is proposed to be involved in sensory perception [142], but has limited annotations otherwise.…”
Section: Important Implications For Acid Sensing Ion Channels In Fligsupporting
confidence: 51%
“…Rbfox1 binding to introns causes context-dependent exon retention or skipping, depending on if it binds upstream or downstream of an alternative exon (Fukumura et al, 2007;Nakahata and Kawamoto, 2005), while 3'-UTR binding is reported to modulate mRNA stability (Carreira-Rosario et al, 2016). Rbfox1 may additionally influence transcription networks by binding transcriptional regulators (Shukla et al, 2017;Usha and Shashidhara, 2010;Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Septin 7 was identified as a novel ERK3-interacting protein by using a Ras recruitment system, and evidence showed that Sept7, ERK3 and MK5 exist in the same complex and, together with Kal7, are of physiological relevance in neuronal plasticity by regulating dendritic spine formation (63). Furthermore, Ataxin-2 was described as a positive regulator of Notch signaling (64), which may maintain NF-ÎșB activity by direct interaction with p50/c-Rel in the nucleus (65). Thus, we can conclude that there is an indirect association with the current and previous results due to the overlapping functions and interactions of multiple proteins involved in the NF-ÎșB and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%